Factors influencing market risk of Maybank Bhd / Nabila Hanin Mazli - Mazli, Nabila Hanin (Faculty of Business and Management, 2010)
Market risk is the risk to earnings arising from changes in interest rates or exchange rates, or from fluctuations in bond, equity or commodity prices. Banks are subject to market risk in both the management of their balance sheets and in their trading operations. The purpose of this study is to determine the main factor that influences the market risk of the Maybank Bhd. Furthermore, it is also conduct in order to identify the relationships between the independent variables and dependent variables. Secondary data is use due to analyze the data for my research where the researcher get from the Maybank Bhd and Bank Negara Malaysia website and also from Indexmundi.com. There are two types of analysis in SPSS program that had been used in the study to analyze the data correlation and regression. In addition, this studies also using Microsoft Excel to calculate the data. The study is done in order to find the factors that influence the market price of Maybank Bhd. Beside that, the study is also done to explain about the relationships of the factors; interest rate, exchange rate, and commodity price towards the market price. The researcher found that the main factor influencing the market risk of Maybank is interest rate and there are two independent variable (interest rate and exchange rate) that have relationship with dependent variable (market price). But, for commodity price, there are no relationship with the dependent variable.